A randomised clinical study comparing the effect of Steareth 30 and SLS containing toothpastes on oral epithelial integrity (desquamation). (January 2019) - Green, A.; Crichard, S.; Ling-Mountford, N.; Milward, M.; Hubber, N.; Platten, S.; Gupta, A.K.; Chapple, I.L.C.
Abstract: Objective: To compare the clinical effect of toothpastes containing Steareth 30 and SLS (sodium lauryl sulphate) surfactants on oral epithelial integrity (desquamation) using a new Oral Mucosal Sloughing Index (OMSI). Methods: 30 volunteers participated in a single centre, double-blind, randomised, crossover clinical study. After a lead-in, subjects were allocated to the first test toothpaste, which was applied to the maxilla via a cap splint, followed by whole mouth brushing with the respective toothpaste and rinsing with the toothpaste slurry. Soft desquamation (lesion status) was assessed using a novel Oral Mucosal Sloughing Index (OMSI). Soft tissue status was measured at baseline (prior to test product use), 30 min following test product application and 4 days later following "at home" use of test toothpaste. After a wash out period, soft tissue assessment and product use were repeated for the remaining toothpaste. Results: Using the OMSI, 30 min post-application, significantly fewer lesion counts (all sites) were observed for the Steareth 30 toothpaste compared to SLS toothpaste (p < 0.0001). Additionally, 30 min after toothpaste use, the average lesion severity score was significantly lower for the Steareth 30 toothpaste compared to SLS toothpaste (p < 0.0001). There were no significant differences in lesion status at baseline or following 4 days of "at home" use of the toothpastes. No product related adverse events were reported. Conclusion: Using an Oral Mucosal Sloughing Index for assessment, application of a toothpaste containing Steareth 30 generated significantly less transient soft tissue desquamation (fewer lesion counts and lower severity) than a toothpaste containing SLS. Clinical Significance: Treatment with a toothpaste containing Steareth 30 surfactant generated fewer transient soft tissue lesions (lower desquamation) compared to a toothpaste containing SLS surfactant.